Exploring the Experiences of Sexual Violence/Abuse Survivors Attending a Recovery Group: A Qualitative Study of Recovery and Evaluation Implications - Meyrick, Jane (Violence against women, 2025)
Sexual violence/abuse (SV/A) is increasingly recognized requiring improved, evidence-based treatments. Delivery of group-based support in survivor services is common but often lacks evaluation. This qualitative study explored how survivors experienced groups and wanted recovery measured. Semistructured interviews with survivors of SV/A from two groups (N = 13, female: 25–64 years: mainly White British, heterosexual) were analyzed using an inductive approach to thematic analysis. Three overarching themes were identified including “anger,” recovery “in the company of” others and “different destinations.” The work contributes recognition of the need for evaluation with meaning to survivors and the potential for anger to be used in group activism.